Implementasi Program Kampung Iklim di Desa Margagiri Kecamatan Bojonegara Kabupaten Serang - Wita Oktavia; Ipah Ema Jumiati (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2026)
Climate change has encouraged the Indonesian Government to implement the Climate Village Program (ProKlim) as a community-based policy for climate change adaptation and mitigation. This study aims to analyse the implementation of ProKlim in Margagiri Village, which has received the ProKlim Utama designation. The study employed a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and document review involving village officials, programme implementers, community members, and related stakeholders. Data were analysed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing. Data validity was ensured through source triangulation, technique triangulation, and member checking. The analysis used the policy implementation model of Van Meter and Van Horn, covering policy standards and objectives, resources, characteristics of implementing agencies, implementers’ disposition, inter-organisational communication, and the social, economic, and political environment. The findings indicate that ProKlim implementation in Margagiri Village has generally progressed well, supported by clear programme objectives, funding from the regional budget, corporate social responsibility, and community contributions, as well as positive commitment among implementers. Nevertheless, several obstacles remain, including limited personnel, uneven community participation, overlapping roles among programme managers, underutilised public green spaces, limited academic involvement, and unequal access to information for women. The study recommends strengthening managerial capacity, optimising household yard utilisation, expanding collaboration with universities and companies, and ensuring women’s meaningful participation in programme planning and decision-making.